CEACAM1: Expression and Role in Melanocyte Transformation. (24th August 2016) - Turcu, Gabriela; Nedelcu, Roxana Ioana; Ion, Daniela Adriana; Brînzea, Alice; Cioplea, Mirela Daniela; Jilaveanu, Lucia Beatrice; Zurac, Sabina Andrada
Abstract : Metastases represent the main cause of death in melanoma patients. Despite the current optimized targeted therapy or immune checkpoint inhibitors the treatment of metastatic melanoma is unsatisfactory. Because of the poor prognosis of advanced melanoma there is an urgent need to identify new biomarkers to differentiate melanoma cells from normal melanocytes, to stratify patients according to their risk, and to identify subgroups of patients that require close follow-up or more aggressive therapy. Furthermore, melanoma progression has been associated with the dysregulation of cell adhesion molecules. We have reviewed the literature and have discussed the important role of the expression of the carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1) in the development of melanoma. Thus, novel insights into CEACAM1 may lead to promising strategies in melanoma treatment, in monitoring melanoma patients, in assessing the response to immunotherapy, and in completing the standard immunohistochemical panel used in melanoma examination.